Causal Associations of Obesity With the Intervertebral Degeneration, Low Back Pain, and Sciatica: A Two-Sample Mendelian Randomization Study - Zhou, Jingzhu; Mi, Jiarui; Peng, Yu; Han, Huirong; Liu, Zhengye (Frontiers in Endocrinology, 2021)
The role of obesity in the development of dorsopathies is still unclear. In this study, we assessed the associations between body mass index (BMI) and several dorsopathies including intervertebral disc degeneration (IVDD), low back pain (LBP), and sciatica by using the Mendelian randomization method. We also assessed the effect of several obesity-related traits on the same outcomes. Single nucleotide polymorphisms associated with the exposures are extracted from summary-level datasets of previously published genome-wide association studies. Summary-level results of IVDD, LBP, and sciatica were from FinnGen. In our univariable Mendelian randomization analysis, BMI is significantly associated with increased risks of all dorsopathies including sciatica (OR=1.33, 95% CI, 1.21-1.47, p=5.19×10-9), LBP (OR=1.28, 95% CI, 1.18-1.39, p=6.60×10-9), and IVDD (OR=1.23, 95% CI, 1.14-1.32, p=2.48×10-8). Waist circumference, hip circumference, whole-body fat mass, fat-free mass, and fat percentage, but not waist-hip ratio were causally associated with increased risks of IVDD and sciatica. Higher hip circumference, whole-body fat mass, fat-free mass, and fat percentage increased the risk of LBP. However, only whole-body fat-free mass remained significant association with the risk of IVDD after adjusting for BMI with an odds ratio of 1.57 (95% CI, 1.32-1.86, p=2.47×10-7). Proportions of BMI’s effect on IVDD, sciatica, and LBP mediated by leisure sedentary behavior were 41.4% (95% CI, 21.8%, 64.8%), 33.8% (95% CI, 17.5%, 53.4%) and 49.7% (95% CI, 29.4%, 73.5%) respectively. This study provides evidence that high BMI has causal associations with risks of various dorsopathies. Weight control is a good measure to prevent the development of dorsopathies, especially in the obese population.